Impact of oral health on quality of life of diabetic elderly in a family health unit - Soraya Fernandes Mestriner; Luana Pinho de Mesquita Lago; Fernanda Bortolotti; Rai Matheus Carvalho Santos; Leandro Dorigan de Macedo; Wilson Mestriner Júnior (Associação Brasileira de Odontologia, 2018)
Objective: to analyze the impact of oral health on the quality of life of elderly diabetics attended in a family health unit. Material and Methods: this was a descriptive cross-sectional exploratory study with the application at home of the Oral Health Impact Profile questionnaire - OHIP-14 and a questionnaire on socioeconomic evaluation, reported oral morbidity, use of dental services, self-perception in oral health and adherence to healthy practices for the control of Diabetes Mellitus (DM). The data were submitted to bivariate analysis and non-parametric Mann-Whitney statistical tests for comparisons and Spearman's for correlations, with a significance level of 5%, in order to determine the association between the OHIP-14 and the independent variables analyzed. Results: a total of 86 elderly diabetics, with a mean age of 70 years, mostly female, with per capita family of up to 1 minimum wage and literate. The total OHIP-14 average was 6.34. The domains that presented the most significant impact (p